ANALISIS KEBUTUHAN TERHADAP PENGEMBANGAN INSTRUMEN PENILAIAN OTENTIK DI MADRASAH ALIYAH NEGERI 2 KOTA BENGKULU - Detti Lismayanti (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2015)
The aim of Curriculum 2013 is to make a renewal in education. The renewal connected to the teaching renewalwith its devices including its evaluation. Teachers are hoped to evaluate with authentic instumen evaluation. Butin the application, teachers have many constraints to do it. The problems in this research are: (1)What authenticevaluation models which applied by teachers of English at MAN 2 Kota Bengkulu, (2) What are the steps that isused by teachers of English at MAN 2 Kota Bengkulu? (3) What are the constraints that faced by teachers ofEnglish at MAN 2 Kota Bengkulu? (4) What are the efforts that is made by teachers of English at man 2 KotaBengkulu? (5) What is the need of English teachers in developing authentic evaluation instruments at MAN 2Kota Bengkulu? The sample of this research is census sample, that is all individual in the population are chosento be sample. Census is taken because the number of population is small. The are 4 teachers to be the sample inthis research. Based on the analysis English teachers had problems in applying the authentic evaluation. Theteachers had done all of the instuments of authentic evaluation to the students. The constraints are the limit oftime, facilities and infrastructures, the difficulties in appliying authentic evaluation of specific competency, haveproblems of about the students. The teachers of English at MAN 2 Kota Bengkulu did the efforts to resolve theconstraints in applying the constraints.The efforts are adapted as its constaints faced.This shows that teacherstried to apply authentic evaluation well and suitable to applicabled curriculum. Teachers of English at MAN 2Kota Bengkulu tried to apply authentic evaluation appropriately. The teachers decide the standard, the model,the criteria, making the rubric, socialize the instument to the students, do the evaluation and give score. Theanalysis of teachers’ need, the teachers have to learn more in developing his/her competence of education and inapplying the evaluation appropriate with curriculum.